The Correlation between Students’ Habit of Taking Notes and Their Writing Ability at Senior High School - Raudah Raudah; Yulmiati Yulmiati; Riny Dwitya Sani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study aims to determine the correlation between students' habit of taking notes and their writing ability at senior high school. This type of research is correlational quantitative research. The sample of this research is class XI, 1 class totaling 33 students. In determining the sample, the researcher used the Cluster Random Sampling technique. The research instrument was a questionnaire sheet to measure students' habit of taking notes and the writing test to measure students' writing ability. The data analysis technique was carried out by calculating the Pearson Product Moment Correlation statistic. The results of this study indicate that r-count = 0.358 with an interpretation of r 0.20 - 0.39 so that the level of relationship between the two variables is in the Low Correlation category. While the 5% significant test is 0.344. It is known that r-count is higher than r-table with a significant level of 5% (0,358>0,344) which mean Ha is accepted and Ho is rejected. So the hypothesis of this research is accepted; is there any correlation between students’ habit of taking notes and their writing ability at senior high school? Thus, it can be concluded that there is a significant relationship between students' habit of taking notes and their writing ability at senior high school.Penelitian ini bertujuan untuk mengetahui hubungan antara kebiasaan siswa mencatat dan kemampuan menulis siswa pada tingkat SMA. Jenis penelitian ini adalah penelitian kuantitatif korelasional. Sampel penelitian ini kelas XI yaitu 1 kelas yang berjumlah 33 siswa. Dalam penentuan sampel, peneliti menggunakan teknik Cluster Random Sampling. Instrument penelitian berupa lembaran angket untuk mengukur kebiasaan siswa mencatat dan tes menulis teks deskripsi untuk mengukur kemampuan menulis siswa. Teknik analisis data dilakukan dengan perhitungan statistik Pearson Product Moment Correlation. Hasil penelitian ini menunjukan bahwa r-hitung = 0.358 dengan interpretasi r 0.20 - 0.39 sehingga tingkat hubungan antara dua variabel di kategori Low Correlation. Sedangkan uji signifikan 5% sebesar 0.344. Diketahui r-hitung lebih besar dari r-table dengan taraf signifikan 5% (0,358>0,344) yang berarti Ha diterima dan Ho ditolak. Jadi hipotesis dalam penelitian ini diterima; Apakah ada hubungan antara kebiasaan siswa mencatat dengan kemampuan menulisnya di SMA?. Dengan demikian dapat disimpulkan bahwa terdapat hubungan yang signifikan antara kebiasaan siswa mencatat dan kemampuan menulis siswa pada tingkat SMA.